Targeting myelin lipid metabolism as a potential therapeutic strategy in a model of CMT1A neuropathy - R. Fledrich (Nature Portfolio, 2018)
Charcot–Marie–Tooth disease 1A (CMT1A) is a peripheral demyelinating disease. Here, the authors demonstrate in a rodent model of CMT1A that Schwann cells have impairments in lipid biosynthesis, and that restoring lipids via diet can reverse the dysmyelinating phenotype in these animals.